Maternal education, economic empowerment and infant mortality in Burkina Faso - Lamissa Barro; Aïcha Tiendrebeogo; Issa Nana; Landry Paul Armand Mawuvi Ky (Economies, 2025)
Education levels in Burkina Faso, especially among women, remain low despite efforts made by government authorities and development partners to implement priority area 4 of the Sustainable Development Goals (SDGs). This situation presents difficulties for women in terms of their being economically and socially empowered. At the same time, the infant mortality rate in Burkina Faso is higher than the average for sub-Saharan Africa. This study analyses the combined effect of education level and women's economic empowerment on infant mortality in Burkina Faso. It uses a linear probability model with instrumental variables approach to demographic and health survey data. The results highlight the positive impact of women's level of education, understood in terms of literacy, and of their economic empowerment, in terms of probability of gain and decision-making power. Nevertheless, the impact of mothers' level of economic empowerment remains mixed. Based on the findings of this study, policymakers should strengthen policies related to girls'education, while improving the education system by integrating vocational training into the school curriculum. For better child well-being, mothers' economic empowerment policies must be accompanied by legal measures aimed at eradicating traditional gender norms and sociocultural values restrict which limit their decision-making power.
Keywords: 330; maternal education; economic empowerment; infant mortality